2014
DOI: 10.1590/s1415-47572014000200014
|View full text |Cite
|
Sign up to set email alerts
|

The new world of RNAs

Abstract: One of the major developments that resulted from the human genome sequencing projects was a better understanding of the role of non-coding RNAs (ncRNAs). NcRNAs are divided into several different categories according to size and function; however, one shared feature is that they are not translated into proteins. In this review, we will discuss relevant aspects of ncRNAs, focusing on two main types: i) microRNAs, which negatively regulate gene expression either by translational repression or target mRNA degrada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(56 citation statements)
references
References 124 publications
(140 reference statements)
0
52
0
4
Order By: Relevance
“…In the present study, siRNA technology was used, and double-stranded siRNA targeting β-catenin was synthesized (15)(16)(17). The experimental results indicated that specific siRNA targeting β-catenin could inhibit the expression of the β-catenin gene.…”
Section: Discussionmentioning
confidence: 93%
“…In the present study, siRNA technology was used, and double-stranded siRNA targeting β-catenin was synthesized (15)(16)(17). The experimental results indicated that specific siRNA targeting β-catenin could inhibit the expression of the β-catenin gene.…”
Section: Discussionmentioning
confidence: 93%
“…miR-195 has also been suggested to be useful as a potential diagnostic and therapeutic target for breast cancer (8,9), and has been shown to inhibit bladder cancer cell proliferation by directly targeting CDK4 and GLUT3 (10,11). As one miRNA has multiple targets, and one mRNA can be targeted by numerous miRNAs (12), the underlying molecular mechanisms of miR-195 in bladder cancer, and the existence of other targets of miR-195, remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) belong to a class of small endogenous non-coding RNAs with $22nt that repress mRNA of protein-coding translation by base pairing of the target genes [4]. It has been shown that miRNAs regulate the expression of at least one-third of all human genes [5], and bioinformatics analyses estimate that more than 60% of human protein-coding genes maintain pairing to miRNAs with regulatory roles in cell proliferation, differentiation, apoptosis, pathogenesis of many human diseases and tumorigenesis [6][7][8][9][10][11]. The loss or dysregulation of certain individual miRNAs can have serious physiological consequences [12][13][14].…”
Section: T Cell Receptor (Tcr)abmentioning
confidence: 99%